Prospects For Sustainable Tourism Development In Bima Regency (Tambora National Park Case Study) - M. al-khusaini; M.ulfatulAkbarJafar (CV. Abhinaya Indo Group, 2025)
This study aims to determine the prospects for sustainable tourism development in Mount Tambora National Park and identify factors that are obstacles in its management. Mount Tambora National Park has great tourism potential, both in terms of natural beauty and historical value. This study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that tourism in this region has positive prospects if managed according to sustainability principles. Based on indicators from UNWTO, economic, socio-cultural, and environmental aspects have shown signs of growth, such as community involvement in tourism businesses (homestays, guides, forest honey), preservation of local culture, as well as institutional support from the National Park Office and the Tourism Office. However, several problems are still obstacles, such as the lack of supporting infrastructure, lack of digital promotion, and limited human resource capacity. Efforts to resolve the issue are carried out through training, the formation of tourism awareness groups, the provision of business support tools, and increased coordination between stakeholders. Cross-sectoral collaboration is an important key in realizing the development of tourism that is sustainable, inclusive, and has a real impact on local communities.